Synthesis of Square Planar Cu4 Clusters. (8th September 2022) - Osei, Manasseh Kusi; Mirzaei, Saber; Bogetti, Xiaowei; Castro, Edison; Rahman, Mohammad Azizur; Saxena, Sunil; Hernández Sánchez, Raúl
Abstract: Template‐assisted synthesis of well‐defined polynuclear clusters remains a challenge for [M4 ] square planar topologies. Herein, we present a tetraamine scaffold R L(NH2 )4, where L is a rigidified resorcin[4]arene, to direct the formation of C 4 ‐symmetric R L(NH)4 Cu4 clusters with Cu−Cu distances around 2.7 Å, suggesting metal‐metal direct interactions are operative since the sum of copper's van der Waals radii is 2.8 Å. DFT calculations display HOMO to HOMO‐3 residing all within a 0.1 eV gap. These four orbitals display significant electron density contribution from the Cu centers suggesting a delocalized electronic structure. The one‐electron oxidized [Cu4 ] + species was probed by variable temperature X‐band continuous wave‐electron paramagnetic resonance (CW‐EPR), which displays a multiline spectrum at room temperature. This work presents a novel synthetic strategy for [M4 ] clusters and a new platform to investigate activation of small molecules. Abstract : Polynuclear reaction sites catalyze some of the most challenging transformations in chemistry. Programmatic assembly of atomically‐precise cluster compounds is challenging. Here we describe the synthesis of supramolecular ligands designed to nucleate well‐defined square planar tetranuclear copper clusters, establishing metal‐metal interactions capable of delocalizing oxidation stress across the cluster.